Correction: Influence of Cu doping on the visible-light-induced photocatalytic activity of InVO4. Issue 62 (13th October 2020) - Wetchakun, Natda; Wanwaen, Pimonrat; Phanichphant, Sukon; Wetchakun, Khatcharin
Abstract : Correction for 'Influence of Cu doping on the visible-light-induced photocatalytic activity of InVO4 ' by Natda Wetchakun et al., RSC Adv., 2017, 7, 13911–13918, DOI: ; 10.1039/C6RA27138C .